Genetic analysis of the susceptibility of mouse cytomegalovirus to acyclovir. - Sandford, G R (1985)
Eight independently derived mouse cytomegalovirus (MCMV) mutants resistant to acyclovir (ACV) were obtained by the sequential plating of wild-type virus in increasing concentrations of ACV. Results of complementation studies among these eight mutants suggest that all had mutations within the same or closely associated genes. A ninth MCMV mutant resistant to phosphonoacetate (PAA) derived by plating wild-type virus in the presence of 100 micrograms of PAA per ml displayed coresistance to ACV and was unable to complement any of the ACV-derived mutants. Recombination experiments among all combinations of the nine MCMV mutants were performed and supported the complementation data in that no recombination could be detected. Seven of the eight ACV-resistant mutants demonstrated cross-resistance to PAA and hypersensitivity to aphidicolin. The one mutant not coresistant to PAA was more susceptible to PAA than was the parent virus. Only a few mutants demonstrated coresistance when the mutants were tested against 9-beta-D-arabinofuranosyladenine (ara-A). The ACV mutant that demonstrated increased susceptibility to PAA was 30-fold more susceptible to ara-A but remained unchanged in susceptibility to aphidicolin. Two of the parent-mutant combinations were selected for DNA synthesis analysis in the presence of ACV (5 microM). A significant decrease in DNA synthesis was demonstrated for both parent viruses, and there was little effect on mutant virus DNA synthesis at the same drug concentration. These results suggest that susceptibility of MCMV to ACV is confined to a product of a single gene and that a mutation of this gene can lead to an altered phenotype when compared with parent virus in susceptibility of DNA synthesis to PAA, ara-A, and aphidicolin, drugs that are known to inhibit DNA polymerase activity.